PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MATEMATIK SISWA SMK MELALUI PENDEKATAN PROBLEM POSING - Eka Senjayawati (Universitas Muhammadiyah Pringsewu, 2018)
Abstract The purpose of this research were to know the difference of  achievement and improvement in mathematical critical thinking ability of students that given problem posing approach with students that given conventional learning. The method used in this research is the experimental method, with the design of pretest-posttest control group. The population is all students of vocational school in Cimahi, while the sample is chosen selectively from two classes of one of vocational schools. Then from these two classes, it is determined randomly as to which class is assigned into experimental or control class. In analyzing the data, the test of two mean differences is done using non-parametric statistical test Mann Whitney and the t test. The results show that (1) mathematical critical thinking of the students who received problem posing is better than that of those who received conventional learning; (2) Improvement in mathematical critical thinking ability of the students who received problem posing approach is better than that of those received conventional learning   Keyword: Mathematical critical thinking, Problem posing